2001
DOI: 10.1590/s0073-47212001000200007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of quantities of brewer yeast on the performance of Anastrepha obliqua wild females (Diptera, Tephritidae)

Abstract: Using artificial solid diets, experiments were performed with Anastrepha obliqua (Macquart, 1835) wild females in order to verify the influence of different quantities of brewer yeast on the performance and compensation behavior to unbalanced diets ingestion. The observed parameters were egg production, ingestion, diet efficiency and survival in the reproductive phase. Results indicated that there was no compensatory ingestion to different quantities of yeast and that the diet with 12.5g of yeast provided the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Studies have shown that female fruit flies require higher amounts of amino acids than males, because ingestion of amino acids is necessary for maximal egg development (Fontellas & Zucoloto 1999;Cresoni-Pereira & Zucoloto 2001;Aluja et al 2001). Those studies support the findings of Arredondo et al (2014) and Díaz-Fleischer et al (2009), which found greater attraction of A. obliqua females to different protein attractions in field trials than males of the same species.…”
Section: Discussionsupporting
confidence: 73%
“…Studies have shown that female fruit flies require higher amounts of amino acids than males, because ingestion of amino acids is necessary for maximal egg development (Fontellas & Zucoloto 1999;Cresoni-Pereira & Zucoloto 2001;Aluja et al 2001). Those studies support the findings of Arredondo et al (2014) and Díaz-Fleischer et al (2009), which found greater attraction of A. obliqua females to different protein attractions in field trials than males of the same species.…”
Section: Discussionsupporting
confidence: 73%
“…Accordingly, it may be that the high protein content of the hydrolysed yeast (FN) in our study (Figure ) was responsible for increased egg–larval duration, reduced pupal weight and a drastic reduction in pupal number in 3FN:1LB and 1FN:0LB diets. Overall, although amino acids are essential for larval development (Chang, ), fruit fly larvae might prefer yeasts with optimal quantity or combination of amino acids (Cresoni‐Pereira & Zucoloto, ), less protein, and maybe more carbohydrate and fat (Chang et al., ; Ekesi et al., ). High nutrient concentration in larval diets does not necessarily improve the performance of diets in productivity or fly quality (Pascacio‐Villafán et al., ) and may result in reduced productivity and fly quality or increased waste.…”
Section: Discussionmentioning
confidence: 99%
“…Above this concentration, the percent of matings showed a decreasing tendency. We did not test greater yeast concentrations because our own unpublished observations and results by Cresoni‐Pereira and Zucoloto (2001) on A. obliqua have indicated that these adversely affect survival.…”
Section: Discussionmentioning
confidence: 99%